The Lions Sports Academy TackleTEK Tool: The intra-and inter-coach reliability of assessing tackling competency in rugby union - Robert Owen; Camilla J. Knight; Will Page; Jamie Tallent; Liam Kilduff; Mark Waldron (PLoS ONE, 2026)
Tackling skill tests in rugby aim to evaluate skill competency, but their reliability to detect meaningful changes in tackling competency over time remains uncertain. This study aimed to: 1) determine the intra- and inter-rater reliability of scoring composite tackle competency by three youth grassroots rugby coaches (tier one, two, and three), and 2) assess reliability in scoring across tackling subcomponents (pre-contact, contact, and post-contact) using the Tackle TEK Tool. Pilot data was used to develop a-priori analytical goals to assess the reliability of composite and subcomponent scoring. Non-parametric 95% Limits of Agreement were used to assess reliability. Twenty-five participants were recorded performing the one vs. one tackling assessment. The three coaches scored each tackle against pre-defined 18-point criteria. Systematic differences were assessed using Wilcoxon tests. Intra-coach composite tackling scores demonstrated agreement levels of 72% (95% CI 60% to 84%) for the tier three coach, and 100% (95% CI 100% to 100%) for both the tier two and one coaches, relative to the analytical goal. Inter-coach composite tackling agreement ranged from 78% (95% CI 67% to 89%) to 100% (95% CI 100% to 100%). Intra-coach subcomponent analysis showed the tier one and tier two coach to score all tackling subcomponents consistently ( P > 0.05); however, the tier three coach only reliably scored the pre-contact phase. Subcomponent agreement ranged from 68% (95% CI 55% to 81%) to 82% (95% CI 71% to 93%), between tier three and tier one coaches, to 72% (95% CI 60% to 84%) to 98% (95% CI 94% to 100%), between tier two and tier one coaches. Within the context of this study, agreement was strongest for tier one and tier two coaches, supporting the use of the Tackle TEK Tool to assess changes in tackling competency over time, with further work required to extend its application across coaching levels.